1ISG-024 Biosimilars switch: do doctors and patients revert back after switching?. (March 2019) - Cardona Pascual, I; Alonso, C; Berlana, D; Mariaqueralt Gorgues, MN; Rosa, G; Marta, D
Abstract : Background: Biosimilars are a great opportunity to improve the efficiency of health systems. Their quality is certified by regulatory agencies and high-quality clinical trials. However, some reluctance about switching between originals and biosimilars still remains between doctors and patients because of different reasons. Purpose To determine if doctors or patients revert back to initial treatment after switching between biologic originals and biosimilars in real life. Material and methods: Electronic prescriptions were used to identify all patients under biologic treatment who had a biosimilar available. Rituximab (Mabthera, Rixathon), etanercept (Enbrel, Benepali, Erelzi), infliximab (Remicade, Inflectra, Remsima) and filgrastim (Neupogen, Accofil) where considered. Darbepoetin (Aranesp), peg-eritropoetin beta (Mircera) and biosimilar eritropoetin alpha (Binocrit) were considered despite not being biosimilars because the hospital Formulary Committee agreed the switch between them. Patients switched from original to biosimilar or vice versa when selected for evaluation. If treatment remained unchanged after the switch until the time of evaluation it was considered successful, understanding that both the patient and the doctor where satisfied. If the change was reverted, the clinical file was reviewed to assess the reason. Results: Between September 2015 (first biosimilar prescription) and September 2018 5909 patients were treated with the above-mentioned biologics: 874 received a biosimilar but only 250 had a switch. Switch description: Etanercept: 41 patients Enbrel to Erelzi, four patients Enbrel to Benepali, three patients Benepali to Erelzi, no switch reverted. Infliximab: 34 patients Remicade to Infectra, one patient Inflectra to Remicade, no switch reverted. Eritropoetins: 12 patients Aranesp to Binocrit, no switch reverted. Filgrastim: 116 patients (74.4%) Neupogen to Accofil and 12 patients (7.7%) Accofil to Neupogen, 26 patients (16.7%) had one or more switches (mostly because of drug shortages) and two patients (1.3%) switched because of patient (fatigue) or doctor (inefficacy) decision. Conclusion: Despite initial reluctance to switch, no significant problems were identified. Monitoring switch reversion is a useful tool to monitor problems when introducing biosimilars and may help to implement early actions if problems are detected. Deeper analysis should be considered to evaluate changes from biosimilars to different drugs after switch. References and/or acknowledgements: Thanks to all authors for their collaboration. No conflict of interest.